Does US foreign policy towards drug-producing states undermine its other foreign policy objectives and interests? - Dobson, Jeremy (2018)
Since the Reagan administration, the US has defined drugs primarily as a threat to its national security interest. It has, therefore, used its global influence to implement methods of narcotics control in foreign states in which drug production and trafficking are prevalent. This conforms to the realist perspective in international relations which considers states to be motivated by their interests. This dissertation will use a single case study of US foreign policy towards Colombia, from 1981 to 2017, to explore whether US foreign policy, informed by its interest to curb drug trafficking, is counterproductive to meeting other key objectives. It argues that the US drug control efforts have continually created unintended consequences which undermine several other core US interests: specifically, national security in relation to counterinsurgency, economic interests concerning natural resources and its ability to maintain credibility in respect of human rights.